The world is flat : a brief history of the globalized world in the twenty-first century - Friedman, Thomas L. (London : Allen Lane, 2005)
"The World Is Flat is a timely and essential update on globalization, its successes and discontents, illuminated by one of our most respected journalists."--Jacket.
Includes index.
Keywords: Diffusion of innovations; Information society; Globalization -- Social aspects; Globalization -- Economic aspects; Innovations -- Diffusion; Diffusion of innovations; Globalization -- Economic aspects; Information society